Al-Jahiz Criticism Standards of Elocution - Hassan, Nasreddin Ibrahim; Alsalmi, Haitham Ahmed (Journal of Humanities & Social Sciences, 2021)
Elocution has originated in ancient times and developed as a unique form of art compared to other realms of discourse. It has developed over time beyond the simple objective of self-expression to a means of persuasion and motivation of public audiences. Parallel to the expansion of urbanization, the birth of elocution was necessary as it played a central role to encompass many aspects of life and a wide variety of domains. From the divergent opinions that call for the unity of thought, to the persuasion in public forums or as a crucial tool to influence the audience. If we consider the previous faiths and beliefs (language science), we can easily understand the necessity of elocution as a distinctive art.In fact, elocution is a product of intellectual refinement and social progress. It commonly flourished throughout times in public settings and used for a specific purpose and certain situations. It has gained distinct style and elements up until documentation was made possible. It has, since then, evolved significantly from its early beginnings to become a symbol of high status for the civilized and sophisticated nations.In this study we will try to (distinguish patterns in language and its uses) shed light on elocution as a subject and form of art without tedious elaboration or distorting abbreviation. We will study the elocution within Al-Jahiz (159-255H) works of literature. The motive for probing this brilliant artist is primarily due to his encyclopedic knowledge. He was a seasoned intellect that enables the reader to navigate different Arab and western cultures while communicating and comparing between the Arab and other nations’ works of literature.The importance of this study, which adopted the descriptive method and content analysis, lies in the fact that it represents a significant addition to the Arabic prose by showcasing the artistic value and the beautiful styles in his discourse and the elements of such discourse that allow the interested researchers to tackle its subjects and diversity. More important, of course, is to bring to the spotlight this one-of-a-kind artist and prose writer standards with regard to Arabic elocution.Among the most prominent findings of the study is that the foundations on which the art of elocution is based Al-Jahiz are five pillars, which are (typography, narration, eloquence, pronouncement).
Keywords: linguistic patterns; rhetoric; influence on addressees; components of rhetoric; artistic value